Factors influencing the implementation of early discharge hospital at home and admission avoidance hospital at home: a qualitative evidence synthesis - Wallis, Jason A; Shepperd, Sasha; Makela, Petra; Han, Jia Xi; Tripp, Evie M; Gearon, Emma; Disher, Gary; Buchbinder, Rachelle; O'Connor, Denise (Cochrane database of systematic reviews, 2024)
Worldwide there is an increasing demand for Hospital at Home as an alternative to hospital admission. Although there is a growing evidence base on the effectiveness and cost-effectiveness of Hospital at Home, health service managers, health professionals and policy makers require evidence on how to implement and sustain these services on a wider scale. (1) To identify, appraise and synthesise qualitative research evidence on the factors that influence the implementation of Admission Avoidance Hospital at Home and Early Discharge Hospital at Home, from the perspective of multiple stakeholders, including policy makers, health service managers, health professionals, patients and patients' caregivers. (2) To explore how our synthesis findings relate to, and help to explain, the findings of the Cochrane intervention reviews of Admission Avoidance Hospital at Home and Early Discharge Hospital at Home services. We searched MEDLINE, CINAHL, Global Index Medicus and Scopus until 17 November 2022. We also applied reference checking and citation searching to identify additional studies. We searched for studies in any language. We included qualitative studies and mixed-methods studies with qualitative data collection and analysis methods examining the implementation of new or existing Hospital at Home services from the perspective of different stakeholders. Two authors independently selected the studies, extracted study characteristics and intervention components, assessed the methodological limitations using the Critical Appraisal Skills Checklist (CASP) and assessed the confidence in the findings using GRADE-CERQual (Confidence in the Evidence from Reviews of Qualitative research). We applied thematic synthesis to synthesise the data across studies and identify factors that may influence the implementation of Hospital at Home. From 7535 records identified from database searches and one identified from citation tracking, we included 52 qualitative studies exploring the implementation of Hospital at Home services (31 Early Discharge, 16 Admission Avoidance, 5 combined services), across 13 countries and from the perspectives of 662 service-level staff (clinicians, managers), eight systems-level staff (commissioners, insurers), 900 patients and 417 caregivers. Overall, we judged 40 studies as having minor methodological concerns and we judged 12 studies as having major concerns. Main concerns included data collection methods (e.g. not reporting a topic guide), data analysis methods (e.g. insufficient data to support findings) and not reporting ethical approval. Following synthesis, we identified 12 findings graded as high (n = 10) and moderate (n = 2) confidence and classified them into four themes: (1) development of stakeholder relationships and systems prior to implementation, (2) processes, resources and skills required for safe and effective implementation, (3) acceptability and caregiver impacts, and (4) sustainability of services. Implementing Admission Avoidance and Early Discharge Hospital at Home services requires early development of policies, stakeholder engagement, efficient admission processes, effective communication and a skilled workforce to safely and effectively implement person-centred Hospital at Home, achieve acceptance by staff who refer patients to these services and ensure sustainability. Future research should focus on lower-income country and rural settings, and the perspectives of systems-level stakeholders, and explore the potential negative impact on caregivers, especially for Admission Avoidance Hospital at Home, as this service may become increasingly utilised to manage rising visits to emergency departments.